STIM1-dependent peripheral coupling governs the contractility of vascular smooth muscle cells - Vivek Krishnan; Sher Ali; Albert L Gonzales; Pratish Thakore; Caoimhin S Griffin; Evan Yamasaki; Michael G Alvarado; Martin T Johnson; Mohamed Trebak; Scott Earley (eLife, 2022)
Peripheral coupling between the sarcoplasmic reticulum (SR) and plasma membrane (PM) forms signaling complexes that regulate the membrane potential and contractility of vascular smooth muscle cells (VSMCs). The mechanisms responsible for these membrane interactions are poorly understood. In many cells, STIM1 (stromal interaction molecule 1), a single-transmembrane-domain protein that resides in the endoplasmic reticulum (ER), transiently moves to ER-PM junctions in response to depletion of ER Ca2+ stores and initiates store-operated Ca2+ entry (SOCE). Fully differentiated VSMCs express STIM1 but exhibit only marginal SOCE activity. We hypothesized that STIM1 is constitutively active in contractile VSMCs and maintains peripheral coupling. In support of this concept, we found that the number and size of SR-PM interacting sites were decreased, and SR-dependent Ca2+-signaling processes were disrupted in freshly isolated cerebral artery SMCs from tamoxifen-inducible, SMC-specific STIM1-knockout (Stim1-smKO) mice. VSMCs from Stim1-smKO mice also exhibited a reduction in nanoscale colocalization between Ca2+-release sites on the SR and Ca2+-activated ion channels on the PM, accompanied by diminished channel activity. Stim1-smKO mice were hypotensive, and resistance arteries isolated from them displayed blunted contractility. These data suggest that STIM1 – independent of SR Ca2+ store depletion – is critically important for stable peripheral coupling in contractile VSMCs.